Treatment in patients with osteoarthritis at different sites: Place of slow-acting drugs - N. V. Chichasova; G. R. Imametdinоva (Современная ревматология)
The main goal of osteoarthritis (OA) treatment is to perform rational analgesic and anti-inflammatory therapy, to slow down the progression of the disease, and to preserve quality of life in patients. The performance of analgesic therapy in the elderly is impeded by the presence of a concomitant disease, primarily that of the cardiovascular system and gastrointestinal tract. A group of experts has elaborated the algorithm for managing OA patients, which tracks a careful approach to using nonsteroidal anti-inflammatory drugs and confirms the efficacy of slow-acting agents (chondroitin sulfate (CS) and glucosamine) and intraarticular hyaluronate. The experts have concluded that the use of symptomatic slow-acting drugs for the treatment of OA (SYSADOA), if need be, in combination with short-term paracetanol cycles as basic therapy for this condition is safer and more effective. The 2003 EULAR guidelines identify CS and glucosamine as chondroprotectors. Many studies have shown that CS and glucosamine have a moderate or significant effect on joint pain syndrome and functional mobility in OA; they are safe and characterized by minimal side effects. Long-term qualitative randomized controlled trials have demonstrated that CS and glucosamine are able to slow down the progression of joint space narrowing in OA. It is also shown that the use of a combination of glucosamine and CS allows cartilage loss to be prevented.